Erythropoietin Ameliorates Oxidative Stress and Tissue Injury following Renal Ischemia/Reperfusion in Rat Kidney and Lung - Ardalan, Mohammad Reza (Med Princ Pract, 2012)
OBJECTIVE: To study the effect of erythropoietin (EPO) treatment on renal and lung injury following renal ischemia/reperfusion (I/R). MATERIALS AND METHODS: Thirty male Wistar rats were assigned to three groups of 10 rats each. The first group was sham-operated, the second was subjected to renal I/R (30 min of ischemia followed by 24 h of reperfusion). The third group was subjected to renal I/R and treated with EPO in two doses: the first dose 1 h prior to ischemia (1,000 U/kg) and the second dose 6 h after ischemia (1,000 U/kg). RESULTS: The renal and lung tissue injury index, tissue serum blood urea nitrogen and creatinine (Cr) were higher in the renal I/R group compared to the renal I/R + EPO group; the difference was statistically significant (p < 0.05). Kidney and lung tissue glutathione peroxidase and superoxide dismutase levels were higher in the renal I/R + EPO group than the renal I/R group; the difference was also statistically significant (p < 0.05). CONCLUSION: The data showed that EPO pretreatment could be effective in reducing renal and lung injury following renal I/R and could improve the cellular antioxidant defense system. Hence EPO pretreatment may be effective for attenuating renal and lung injury after renal I/R-induced injury during surgical procedures, hypotension, renal transplantation and other conditions inducing renal I/R.